(untitled) (Journal of Sustainability, Environment and Peace, 2019)
Changes in the Lake Victoria basin rainfall regime has far reaching environmental, hydrological and socio-economic effects to the more than 30 million people living around the lake. Lake Victoria basin water balance has rainfall as the main input, contributing about 80% of the input. Rainfall variability therefore plays a key role in the availability of surface water resources in the Lake Victoria basin. The objective of this study was to establish the relationship between Climate Variability and spatial distribution of Surface Water Resources in Homa Bay County. The rivers Kibuon, Tende and Riana are studied. Secondary data sets including climate data which are both in-situ and proxy data were sourced from Kenya Meteorological Department and the Global Weather Database for the period 1986-2012. River discharge data for 30 years spanning from 1983 to 2013 was obtained from Water Resources Authority while the Soil and Water Assessment Tool model (SWAT) was used in the estimation of weather variables including precipitation, temperature, wind speed, relative humidity and solar radiation. Correlation, regression and time series analysis which largely relies on the SWAT model output data were used to determine the relationship between climate variability and surface water resources in relation to availability, distribution and Yield of surface water systems. Impacts of variability in rainfall and temperature trends on surface water resources was discovered in distribution and quantity of water yield These findings will be useful in management of water resources within Homa Bay county and also aid in planning based on rainfall forecasts to avert water crisis scenarios in the county.